Drogas y género en el ámbito penitenciario - Iñaki Markez; Graciela Silvosa Rodríguez (Oñati Socio-Legal Series)
It analyzes the health status of the female prison population in order to contribute to the description and understanding of inequalities, in order to promote health equity and gender analysis of the determinants that influence health outcomes in men and women. Carefully in the consumption of psychoactive substances and perceived health of men and women prisoners and prison policies aimed at women with psychoactive substance dependence, paying attention to the study and treatment.